Towards increasing diversity in the study of religion. Issue 1 (2nd January 2020) - Day, Abby
ABSTRACT: The study of religion needs to be enriched by more diverse voices. The author argues that some progress has been made, but more needs to be done, particularly through collaborating with those most frequently muted. The challenge is to not simply to include those outside the traditional bastions of white, male privilege in the global north, but to actively widen the current reach to make an impact on how knowledge is actually created and shared. Initiatives such as liberating and de-colonizing the curriculum are discussed, with particular reference to the study of religion.